Challenges Faced by Higher Education Institutions in Including Students with Hearing Impairment - Abdul Hameed, Qurrat-ul-Ain (JIE, 2024)
Inclusion at higher education is a recent initiative of Higher Education Commission, Pakistan. Students with hearing impairment and students with visual impairment are welcomed by several HEIs in Punjab. However, the case of students with hearing impairment emerged as very challenging because of limited communication between teacher and taught and ill preparedness of HEIs to accommodate these students.